2017
DOI: 10.3892/mmr.2017.7304
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an lncRNA-miRNA-mRNA interaction mechanism in breast cancer based on bioinformatic analysis

Abstract: Non-coding RNAs serve important roles in regulating the expression of certain genes and are involved in the principal biological processes of breast cancer. The majority of studies have focused on defining the regulatory functions of long non-coding RNAs (lncRNAs) and microRNAs (miRNAs/miRs), and few studies have investigated how lncRNAs and miRNAs are transcriptionally regulated. In the present study, based on the breast invasive carcinoma dataset from The Cancer Genome Atlas at cBioPortal, and using a bioinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 33 publications
1
56
0
Order By: Relevance
“…Interestingly, both lncRNA and mRNA in the ceRNA network were negatively correlated with miRNA. Previous studies have confirmed that ceRNAs can act as miRNA 'sponges' and this is especially important for cancer and tumor diseases [27,28]. By analyzing the miRNAs in the ceRNA network we found that the target miRNAs ssc-miR-885-5p, ssc-miR-490-5p, ssc-miR-196b-5p and ssc-miR-133b of lncRNAs were all up regulated.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, both lncRNA and mRNA in the ceRNA network were negatively correlated with miRNA. Previous studies have confirmed that ceRNAs can act as miRNA 'sponges' and this is especially important for cancer and tumor diseases [27,28]. By analyzing the miRNAs in the ceRNA network we found that the target miRNAs ssc-miR-885-5p, ssc-miR-490-5p, ssc-miR-196b-5p and ssc-miR-133b of lncRNAs were all up regulated.…”
Section: Discussionmentioning
confidence: 56%
“…24,25 One study reported that UCA1 silencing impaired lung cancer cell proliferation and colony formation by regulation of miR-193a-3p. 24,25 One study reported that UCA1 silencing impaired lung cancer cell proliferation and colony formation by regulation of miR-193a-3p.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 For example, in the collagen, antibody induced arthritis mouse model of RA, shikonin can suppress the inflammation by targeting specific lncRNAs, 14 and in presence of quercetin, the apoptosis of fibroblast-like synoviocytes (FLS) in RA was also blocked, in which the involvement of lncRNA MALAT1 plays a critical role. [15][16][17][18][19][20][21][22] In this study, we attempted to discover how MEG3 affects the proliferation and inflammation of LPS-treated chondrocytes in RA.…”
Section: Introductionmentioning
confidence: 99%